Disharmony of Regional Head Couples (Study of Local Leadership in Central Branch 2005-2019 Period) - Mirendy Wahyu Ferary (Green Publisher Indonesia, 2021)
This study provides an overview of the disharmony of the regional head pairs starting from the administrative formation of Central Bangka Regency to its third period. This study applies the conflict theory proposed by Ralf Dahrendorf who explains that the conflict of interest of each elite can be categorized as a struggle of position by the group that owns the authority position. The disharmony of the regional head pairs of Central Bangka is included in the authoritative conflict model that causes the occurrence of latent conflict between both of them to compete for position structure. This study used a descriptive qualitative method with the primary data obtained from the interview results with the informants including related officials, board members, civil servants, and the regional head pairs. The results of this study portray that the obtained data provide an overview regarding the conflict potential that results in the limited access for the vice-regents to perform government duties that have been regulated by law. Therefore, public and personal interests can no longer be distinguished since both interests are related to the matter of competition or race for the local election. In other words, the regents have another underlying interest to limit the vice-regents’ access to perform the government duties. Meanwhile, the last period has a different case regarding the authority role of the vice-regent to run the government since the regent concentrates individually more on his duties.